Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am trying to solve this system of equations for $s_0$ and $s_1$.

$$ s_0 = s_0 (1 - a) + s_1 b \\ s_1 = s_0 a + s_1 (1 - b) $$

I have tried to solve each equation one at a time:

$$ s_0 = s_0 (1 - a) + s_1 b \\ s_0 - s_0 (1 - a) = s_1 b\\ s_0 a = s_1 b \\ $$

$$ s_1 = s_0 a + s_1 (1 - b) \\ s_1 - s_1 (1 - b) = s_0 a \\ s_1 b = s_0 a $$

Unfortunately, I am only going in circles... eventually, I guessed correctly that $s_0 = \frac{b}{a + b}$ and $s_1 = \frac{a}{a + b}$. How do I actually solve it?

share|cite|improve this question
up vote 1 down vote accepted

You're quite correct that both equations are equivalent to $s_0a=s_1b$, and that isn't enough information to get a single solution. In fact, there are infinitely many solutions to this system.

If $a=b=0$, then both $s_0$ and $s_1$ can be anything. If $b=0$ and $a\neq 0$, then we must have $s_0=0$, but $s_1$ can be anything. If $b\neq 0$, then we must have $s_1=\frac{a}{b}s_0$, but $s_0$ can be anything.

I suspect you may have copied one or both of them down incorrectly, that the problem is mistaken, or that the problem mentioned that $a$ and $b$ aren't both $0$ and asked only for some solution.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.